Understanding Leadership Effectiveness in the wake of challenges: a leadership competency model - Rawat, Samir; Deshpande, Abhijit P.; Boe, Ole; Piotrowski, Andrzej (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this article, researchers will introduce readers to the concept of leadership through perspectives of different schools of leadership thoughts. We intend to bring to notice an important discussion on leadership in military organisations and its implications on non-military organisations and institutions. There is a plethora of literature especially borrowing from military literature, which can set the stage for our understanding of what could make up for a robust leadership model comprising of competencies like- power of personal example and influence, adaptive resilience, making critical decisions amid uncertainty, regulated leadership behaviors and thoughts, preparedness, communicating with teams and building trust.